Bioactivities of endophytic Penicillia from Cupressaceae - Mahdieh Hosseini Moghaddam; Jalal Soltani; Freydoun Babolhavaeji; Javad Hamzei; Sonbol Nazeri; Soheila Mirzaei (Journal of Crop Protection, 2013)
The cypress family, Cupressaceae, has a global dispersion. Currently, endophytic microorganisms from plants are being investigated for their diversity and bioactivities. Here, we aimed at exploration and characterization of cultivable endophytic fungi from foliar tissues of Cupressaceae, i.e. Cupressus arizonica, C. sempervirens var. cereiformis, C. sempervirens var. fastigiata, Juniperus excelsa, Juniperus sp. and Thuja orientalis. Asymptomatic fresh foliar tissues, collected from mature healthy plants, were sterilized and the inner layers were plated on culture media at 26-28 °C for 2-12 weeks, until fungal colonies emerged and were purified. Endophytic Penicillia i.e. Penicillium aurantiogriseum, P. chrysogenum, P. commune, P. echinulatum, P. expansum and P. viridicatum were the dominant fungi recovered. Results indicated that both host plant and geographical location of sampling affected the biodiversity and bioactivity of endophytic Penicillia. Results also indicated that those endophytic Penicillia had significant bioactivities. According to our results, both intra-and extra-cellular secondary metabolites from all isolated Penicillia had significant cytotoxic and antifungal effects against the model fungus Pyricularia oryzae and cypress fungal phytopathogens Diplodia seriata, Phaeobotryon cupressi and Spencermartinsia viticola. Further studies indicated the significant antimicrobial bioactivities of superior Penicillia against model bacteria. Altogether, this study highlights, for the first time, the biodiversity of endophytic Penicillia from Cupressaceae plants and documents their significance for agrochemical/drug discovery and for plant disease biocontrol.